Sports Communication on Social Media and Audience Reactions - Turková, Kateřina (Karolinum, 2025)
This book examines the social media communication of Czech athletes, with a focus on the commercialization of their content. It analyzes the topic from two perspectives: the athletes who share their messages and the fans who receive them, both as sports content and commercial promotion. While research on athletes' social media communication exists in other countries, similar studies have not yet been conducted in the Czech Republic. This study combines a year-long content analysis of selected athletes' Facebook pages with interviews with athletes and their representatives, offering a comprehensive look at the phenomenon. The book is intended for experts and the general public interested in sports communication, social media, and marketing.
Keywords: Žurnalistika a komunikace